Differences in Scapular Orientation Between Standing and Sitting Postures at Rest and in 120° Scaption: A Cross-Sectional Study - McKenna, Leanda; Cornwall, X.; Williams, Sian (2016)
Background: Scapular orientation may be influenced by static body posture (sitting and standing) and contribute to the development of shoulder pain. Therefore, a consistent body posture should be considered when assessing scapular orientation as well as enhancing optimal scapular positioning. Objective: To determine whether there are differences in scapular orientation between standing, neutral sitting, and habitual sitting, while adjusting for spinal posture. Design: A single group randomized repeated measures study. Setting: University laboratory. Participants: Twenty-eight participants with shoulder pain were recruited from the community. Methods: Scapular orientation between standing and seated positions was compared, with the arm by the side and at 120° of glenohumeral scaption. Thoracic kyphosis and lumbar lordosis angles were used as covariates. Main Outcome Measurements: Scapular elevation, lateral translation, upward rotation, and posterior tilt. Results: Scapular orientation was marginally but significantly different between sitting postures for lateral translation (mean 0.5 cm; 95% confidence interval [95% CI] 0.2-0.7 cm); P < .001), upward rotation (mean 3°; 95% CI 1.1-5.0°; P < .001), and posterior tilt (mean 2.3°; 95% CI 0.2-4.3°; P = .009) in the arm by side position. A small-but-significant difference between standing and neutral sitting was found for upward rotation (mean 1.8°; 95% CI 0-3.7°; P = .02), and between standing and habitual sitting for lateral translation (mean 0.6 cm; 95% CI 0-1.1 cm; P =.02) in the arm by side position. Conclusions: The results of this study suggest that scapular orientation can be slightly affected by body posture, although the clinical relevance is uncertain. To enhance scapular upward rotation or posterior tilt, it may be preferable to place the patient in neutral sitting.